Oral Health Behavior and Dental Caries status: A comparative study between rural and urban school-going children in Dhaka Division - Sujan Kanti Nath; Ashek Elahi Noor; Clopa Pina Podder; Mohammad Tawfique Hossain Chowdhury (Update Dental College, 2022)
Introduction: The importance of oral health in children is paramount. Proper techniques of brushing and the influence of fermentable carbohydrates in dental caries should be taught at the early childhood stage. Objective: To estimate the mean deft, DMFT, Oral health-related behavior, and practice among the selected rural and urban school-going children in Bangladesh. Materials and Methods: This was a cross-sectional study carried out among 593 (152 rural and 441 urban children) school children using the purposive sampling technique. Data were collected from 3 urban schools and 1 rural school, using an interview-based structured questionnaire and oral examination. Consent was taken both from the college authority and participants before data collection. Descriptive analysis was performed. Results and Discussion: The study was carried out among 593 school children with an age range between below 5 years to above 15 years old. The majority of the students at urban schools brush their teeth twice daily while most rural school children brush their teeth once daily. Most of the students use toothbrushes and toothpaste as cleaning aids, however, the majority of them usually brush before meals. In addition, the majority of the students at rural and urban schools do not brush their teeth after taking sweet foods. Mean deft in deciduous teeth is high among rural school children (2.07) while mean DMFT in permanent teeth is high among urban schools. Conclusion: Organized and systemic community oral health promotion should be strengthened and a prevention-oriented oral health system is needed for promoting future oral self-care practices among school children. Update Dent. Coll. j: 2022; 12(1): 3-7